Abstract 4125511: L-shaped association of non-high-density lipoprotein cholesterol to high-density lipoprotein cholesterol ratio (NHHR) and arterial stiffness: a cross-sectional study - Wei, Taotao; LIN, XIN; Yu, Jing (Circulation (New York, N.Y.), 2024)
Background: Serum lipids and ratios are known to be associated with cardiovascular disease (CVD). However, studies on NHHR and the association with arterial stiffness in the US population have not been reported. We sought to investigate the relationship between NHHR and arterial stiffness by arterial stiffness in subjects from the US population assessed by ePWV. Methods: This study included 23, 456 adults from the National Health and Nutrition Examination Survey (NHANES) spanning from 2007 to 2016. Multivariate linear regression analysis, threshold effects, smooth curve fitting, and subgroup analysis. We aimed to elucidate the relationship between NHHR and risk of arterial stiffness. Results: The mean age of the population in this study was 49.56 ± 17.58 yrs. The mean NHHR was 2.97 ± 1.48, and in the fully adjusted model, a negative correlation was observed between NHHR and ePWV scores (β = -0.01, 95% CI: -0.02, -0.00), with the highest tertile of the NHHR having a mean ePWV score that was 0.06 units lower than the lowest quartile of the NHHR by 0.06 units (β = -0.06, 95% CI: -0.09, -0.02; P for trend = 0.0068). An L-shaped relationship between NHHR and ePWV scores was found by using smoothed curve fitting. The cutoff value was 2.13, and in the hypertensive population, the cutoff value was 1.93. Conclusions: There is an L-shaped association between NHHR levels and atherosclerosis in adults in the United States, and controlling NHHR is clinically important for reducing the risk of developing atherosclerosis.